Impact of Internet on Academic Performance of University Students in Pakistan - Nawaz, Nimra (European Scientific Journal, ESJ, 2021)
It is impossible to ignore the fact that the internet is the basic need of today’s technological world. Different research shows that individuals across the globe are using information and communication technologies (ICTs) to get the most up-to-date information from the internet. Similarly, university students also spend a lot of time on the internet researching and collecting material relevant to their research topics. Although different research has been conducted on the usage of the internet in different countries, research about Pakistani students is still limited. The major goal of this research was to see how internet usage affects students’ academic performance particularly when it comes to increasing their grades. The objective of this research was to determine the type of internet use and the impact of the internet on students’ academic achievement. Arts faculty from the University of Punjab Pakistan was selected as the universe of the study and 5 departments of arts were selected by simple random sampling and a sample of 100 students was taken through systematic sampling. The study adopted a survey research design. A questionnaire was developed by the researchers as a tool for data collection. The data was analyzed statistically, which led to the acceptance of the alternative hypothesis. Statistical results are also presented and discussed, and implications for future research are also provided. According to the findings, internet use has a positive impact on student’s academic achievement.